Clinical Predictors of Early Treatment Failure After Tube Thoracostomy in First-Episode Primary Spontaneous Pneumothorax - Tuba Şahinoğlu; Dursun Öz; Kübra Altıntaş; Atilla Can; Hüseyin Yıldıran (Journal of Medical Topics and Updates, 2026)
Objective: Early treatment failure following initial tube thoracostomy remains a major clinical challenge in patients with first-episode primary spontaneous pneumothorax (PSP). This study aimed to identify clinical predictors of early treatment failure and evaluate its association with short-term clinical outcomes.Materials and Methods: This retrospective single-center study included 80 consecutive patients with first-episode PSP treated with initial tube thoracostomy between January 2014 and January 2026. Early treatment failure was defined as persistent air leak 48 hours after tube insertion despite a functioning drainage system. Demographic, laboratory, and radiological variables were analyzed using univariable and multivariable binary logistic regression. Receiver operating characteristic (ROC) analysis was performed for continuous variables.Results: Early treatment failure occurred in 39 patients (48.8%). In univariable analysis, blebs and/or bullae (OR 4.455, 95% CI 1.530–12.969; p=0.006) and residual pneumothorax on the first-day chest radiograph (OR 2.875, 95% CI 1.148–7.200; p=0.024) were significantly associated with early treatment failure. After multivariable adjustment, only the neutrophil-to-lymphocyte ratio remained independently associated (OR 2.201, 95% CI 1.088–4.452; p=0.028). Early treatment failure was associated with prolonged air leak, increased VATS requirement, longer chest tube duration, and longer hospital stay (all p